Pain and difficulties performing valued life activities in women and men with rheumatoid arthritis - Ahlstrand, I.; Björk, M.; Thyberg, I.; Falkmer, Torbjorn (Springer London, 2015)
This study aimed to examine the difficulties with performing valued life activities in relation to pain intensity in women and men with rheumatoid arthritis (RA). In total, 737 persons with RA (73 % women) from three rheumatology units in Sweden responded to a questionnaire measuring performance of 33 valued life activities and self-rated pain. The relationships between performance of valued life activities (VLAs) and pain (measured by visual analogue scale (VAS)) were analysed based on gender. Multiple linear regression analyses were conducted with the total VLA score as dependent variable. Women reported more pain and difficulties in performing valued life activities than men. Across genders, 85 % reported at least one valued life activity affected by RA. Significantly more women than men encountered difficulties in performing some activities such as cooking, gardening and meeting new people. Women reported higher pain intensity (35 mm) than men (31 mm). Almost all 33 difficulty ratings for valued life activities were higher among persons with high pain (>40 mm) than persons with lower pain. Difficulty ratings for valued life activities correlated positively with pain in persons with lower pain, but not among those with high pain. The results highlight the importance of addressing pain, especially among women with RA, as they reported pain to impact on their valued life activities. Interestingly, this was evident also in women with lower levels of pain.